Niekonwencjonalne metody zarządzania jako odpowiedź na dynamikę zmian w organizacji i otoczeniu - Binsztok, Aleksander (Unconventional methods of management as the answer on the dynamic of changes in the organization and environment, 2006)
In this article an author underlines the need of using the unconventional methods of management. Author presents also practical examples of firms, which on the field of communication, organisation of work, motivation and marketing, in the informal way generate interesting ideas and effectively introduce them to life.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 540-546